Water Resource Conservation Based on Local Wisdom of Madurese Ethnic Migrants in Kalibaru Afdeling Banyuwangi, Indonesia - Slamet Hariyadi; Kamalia Fikri; Arif Fatahillah (JURNAL BIOSHELL, 2022)
Conservation of water resources is very important in the Afdeling area because the water is needed to provide water supply for the plant. The behavior of ethnic Madurese migrants in Kalibaru Afdeling becomes interesting to investigate because it differs from the Banyuwangi indigenous ethnic, Osing. The purpose of this research was to know the habits of the Madurese tribe in the conservation of water resources in the plantation area. This study used a qualitative method with a branched contractile approach, with some informants from three elements such as, residents, community leaders, and village coordinators. The result of this research shows that Sumber Pereng’s inhabitants have some ways to maintain water resource by keeping bamboo and cleaning the area every Rabu Wekasan, while Sumber Limak and Sumber Gueh's inhabitants always change the plants around the water resource, but they do nothing to maintain and conserve it. Water resource conservation is better in Sumber Pereng rather than in Sumber Limak and Sumber Gueh.